Clinical applications of iron oxide nanoparticles for magnetic resonance imaging of brain tumors. (March 2015) - Iv, Michael; Telischak, Nicholas; Feng, Dan; Holdsworth, Samantha J; Yeom, Kristen W; Daldrup-Link, Heike E
Current neuroimaging provides detailed anatomic and functional evaluation of brain tumors, allowing for improved diagnostic and prognostic capabilities. Some challenges persist even with today's advanced imaging techniques, including accurate delineation of tumor margins and distinguishing treatment effects from residual or recurrent tumor. Ultrasmall superparamagnetic iron oxide nanoparticles are an emerging tool that can add clinically useful information due to their distinct physiochemical features and biodistribution, while having a good safety profile. Nanoparticles can be used as a platform for theranostic drugs, which have shown great promise for the treatment of CNS malignancies. This review will provide an overview of clinical ultrasmall superparamagnetic iron oxides and how they can be applied to the diagnostic and therapeutic neuro-oncologic setting.